Persistência comportamental e topografia de controle de estímulos coerente em treino de discriminação simples e escolha condicional por identidade ao modelo com quatro escolhas em macacos-prego (Cebus apella) - RICO, Viviane Verdu (2006)
The objective of this study was to teach to three young adult capuchins, one male and two females, experimentaly naïve, conditional identity matching-to-sample (IDMTS) with four choices, identifying and producing Type S stimulus control topographies which may be favorable for stimulus-class formation. Behavioral persistence was analysed based on stimulus control topography coherence, behavioral momentum theories and on the studies conducted in the Experimental School for Primates. Participants were trained to touch stimuli projected in a computer touchscreen in an experimental chamber and were exposed to a procedure of: 1) Four-choice simple-simultaneous discrimination and shifts of discrimination procedure, with every other trial presenting only the S+, simulating the format of matchingto-sample; 2) IDMTS training with four samples and two or three choices, and the S+ in trial n was not presented as S- in trial n+1; 3) IDMTS training with four choices. Persistent responding in the simple discrimination shift training by M21 was eliminated when the former S+ n was not presented when a new stimulus became S+. The structural similarity between the simple discrimination and IDMTS sessions was not efficient to establish samplecontrolled responding. Subjects M18 and M21 eventually reach IDMTS performance; M20 received additional training with random ratio requirement for the response to the sample and is presenting gradual performance improvement.